Application of Multifunctional Layered Double Hydroxides for Removing Environmental Pollutants: Recent Experimental and Theoretical Progress. Issue 4 (August 2020) - Zhang, Ruihong; Ai, Yuejie; Lu, Zhanhui
Graphical abstract: Abstract: From the first discovery of hydrotalcite in 1842 to the present, the researches of Layered Double Hydroxides(LDHs) have become increasingly mature. Due to its inherent advantages of chemical stability, low cost and non-toxic, it has attracted a great concern within the fields of materials, medicine, environmental treatment, etc. Recent developments of modification methods and composite materials have led to a renewed interest in LDH-based materials as high-performance adsorbents in the removal of the multiple types of pollutants. The paper systematically summarizes the research advance of LDHs and its resultant materials for removing radionuclides, heavy metal ions, anionic and organic pollutants in two aspects: experimental and theoretical calculation. Moreover, the characteristics and modification of LDHs, the adsorption kinetics and isotherm model, the underlying interaction mechanism during the adsorption process have also be elucidated. Compared to the primary LDHs, although the remarkable performance of its composite materials has been made, considering the cost and complexity, greater efforts are needed to ensure its large-scale application. Continued researches of methods are demanded to make LDH materials more accessible to be effective, easier to operate and lower cost, which is also the goal researchers persist.